2019
DOI: 10.18203/2349-3933.ijam20193289
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of microalbuminuria and hypoxemia in patients with chronic obstructive pulmonary disease

Abstract: Background: Microalbuminuria is a sign of glomerular dysfunction in general and sign of tubulointerstitial disease to a lesser extent. Hypoxia induces endothelial cell to release a number of different vasoactive agents including endotheline-1, platelet derived growth factor (PDGF), nitric oxide; that causes endothelial injury and lead to microalbuminuria. This study was aimed to assess the prevalence of microalbuminuria in COPD patients and assess the Relationship of microalbuminuria with the disease severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…9 Poonam et al, study showed that Patients with severe COPD with hypoxemia or hypercapnia were significantly associated with microalbuminuria, similarly in this study also COPD with severity disease is associated with more microalbuminuria. 10…”
Section: Discussionmentioning
confidence: 99%
“…9 Poonam et al, study showed that Patients with severe COPD with hypoxemia or hypercapnia were significantly associated with microalbuminuria, similarly in this study also COPD with severity disease is associated with more microalbuminuria. 10…”
Section: Discussionmentioning
confidence: 99%